A Personal Recovery Approach to Physical Activity for Community Mental Health Service-Users (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Traditionally, mental health services and policy are guided by a clinical recovery approach, but there is an increasing appreciation of adopting person-centred approaches to support positive mental health, often known as personal recovery. Physical activity (PA) is one approach suggested to contribute to personal recovery in community mental health services. However, PA remains scarcely adopted as routine practice and engagement levels remain low. Research is limited in understanding precise mechanisms underlying processes of PA engagement, and how, why, and who can benefit from PA. To address these issues, this realist study evaluated a PA project for service-users within two community mental health teams.Methods: Data were collected using repertory grids and semi-structured interviews, involving 24 service-users and 12 staff members. Interpretative Phenomenological Analysis was used to analyse the data within the broader realist evaluation framework.Results: Findings are best understood as four stages of the participants’ journey through the project. Firstly, it was found that mental health professionals were vital gatekeepers to the PA sessions, either enabling or prohibiting service-user involvement. Secondly, service-users required their priority needs to be met before they could be interested and involved in PA sessions. Thirdly, service-users needed to be both physically and mentally able to access sessions, including considerations of practicalities, emotional support, culture of the sessions, and expectations being managed and met. Finally, once participants were able to access sessions, it was found that PA was beneficial in facilitating service-users’ personal recovery in a positive manner.Conclusion: Exploring and valuing the lived experiences of the service-users was vital to understand underlying mechanisms that contributed to the accessibility and outcomes of PA for personal recovery. Key recommendations include considering how PA is offered within services, especially in terms of facilitating access and support before, during, and after sessions for service-users to participate and aid their personal recovery.Support/Funding Source: Study was funded by Comic Relief (UK Ahead of the Game Fund £424,500, Grant Number 4335581).